ความสัมพันธ์ระหว่างความเข้มแข็งทางใจ การรับรู้ความสำเร็จในอาชีพ ความเชื่อในความสามารถของตนเอง และความตั้งใจในการคงอยู่ในอาชีพนักแปลอิสระ - ปัทมา พัฒนิบูลย์ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
The objective of this study were to study the relationships among resilience, perceived career success, self-efficacy, and intention to stay in freelance translator career; and to study the predictive power of resilience, perceived career success, and self-efficacy on intention to stay in freelance translator career. The sample consisted of 399 freelance translators. Research instruments were Resilience Scale, Subjective Career Success Scale, Translation Self-Efficacy Scale, and Intention to Stay in Translator Career Scale. Descriptive statistic, Pearson’s product moment correlation, and enter selection multiple regression were used to analyze the data. The study found that: 1. Perceived career success and self-efficacy had a positive significant relationship with intention to stay in freelance translator career at the .01 level (r = .236 and .220, respectively). However, resilience had no statistical significant relationship with intention to stay in freelance translator career. 2. Perceived career success and self-efficacy jointly predicted intention to stay in freelance translator career at the .01 level, explaining variance of intention to stay in freelance translator career at 7.9%.